Pengaruh Edukasi Kesehatan Reproduksi tentang Pemeriksaan Payudara Sendiri (SADARI) terhadap Pengetahuan Remaja Putri - Ernawati Anggraeni (ARTERI : Jurnal Ilmu Kesehatan, 2022)
The age of 11 or 12 years to 20 years where sexual maturity occurs and there is a transition from childhood to adulthood is the definition of adolescence, approaching young adulthood. Breast cancer is increasing in developed countries. Breast self-examination (BSE) is used to prevent breast cancer. The purpose of this study was to analyze the effect of reproductive health education on breast self-examination (BSE) on the knowledge of adolescent girls. Design This study used a quast experiment with one group Pre-post Test Design. The results of data analysis from the Effect of Pend mean (average) that the pretest value is smaller than the posttest after a health conscious education is carried out in adolescent girls. The correlation results are said to be very strong if the two samples are paired by 0.381. There is a difference in the knowledge of breast care before and after being given health education to adolescents by analysis using a paired t test which shows a P value of 0.000 with a significant level of 5% (P value < 0.05)